Lymphoblastic lymphomas in children: A single-center experience from Serbia - Lazić Jelena; Janić Dragana; Krstovski Nada; Rodić Predrag; Milošević Goran; Janković Srđa; Brašanac Dimitrije; Dokmanović Lidija (Srpski Arhiv za Celokupno Lekarstvo, 2016)
Introduction. Intensive treatment protocols used for non-Hodgkin lymphoma in children lead to eventfree survival rates ranging from 80% to 90%. However, the results are less successful in developing countries. Lymphoblastic lymphoma (LBL) is the second most frequent type of lymphoma in children, contributing with about one third to all non-Hodgkin lymphoma in childhood. Objective. The aim of the study was to evaluate the results of LBL treatment in University Children’s Hospital (UCH), Belgrade. Methods. A retrospective analysis of patient records at UCH from 1997 to 2015 was carried out in patients aged 0-18 years, in whom the diagnosis of LBL had been established. Twenty-two children were included in the analysis. Results. Mean age at diagnosis was 10 years, with preponderance of male patients. All patients were treated according to Berlin-Frankfurt-Münster-based chemotherapy protocols. With median follow-up of 91.5 months, five-year probability of event-free survival was 79.5% for all patients, while overall survival was 81.8%. Conclusion. Our results, although slightly inferior to those of leading international groups, reflect a good treatment outcome in our patients. [Projekat Ministarstva nauke Republike Srbije, br. 41004]